Two new species of Eugenia (Myrtaceae) from the Cabo Frio Center of Plant Diversity, Rio de Janeiro, Brazil - de Faria, Jair Eustáquio Quintino; Mazine, Fiorella Fernanda; Proença, Carolyn Elinore Barnes (Phytotaxa, 2015)
Two apparently narrow-endemic species of Eugenia are described from the Cabo Frio Center of Plant Diversity in the state of Rio de Janeiro, Brazil. Both present a limited distribution restricted to coastal areas north of Rio de Janeiro. The new species are described and compared with closely related species.  Illustrations, distribution maps and conservation status assessments are also provided. Eugenia gastropogena and Eugenia farneyi are presumably closely related to Eugenia pyriformis and Eugenia malacantha. Eugenia gastropogena can be recognized by its leaves with arched secondary veins not forming a clear marginal vein, subcordate to obtuse leaf bases, petioles 2.1–4.8 mm long, buds 3.5–4 mm long and 2 ovules per locule. E. farneyi can be recognized by having leaves with straight secondary veins that form a single marginal vein running 0.7–1.5 mm from the margin, cuneate leaf bases, petioles 4–6.4 mm long, buds 6.2–8.4 mm long, and 10–12 ovules per locule.